2013
DOI: 10.1111/jgs.12195
|View full text |Cite
|
Sign up to set email alerts
|

Normative Values of Cognitive and Physical Function in Older Adults: Findings from The Irish Longitudinal Study on Ageing

Abstract: Objectives To provide normative values of tests of cognitive and physical function based on a large sample representative of the population of Ireland aged 50 and older. Design Data were used from the first wave of The Irish Longitudinal Study on Ageing (TILDA), a prospective cohort study that includes a comprehensive health assessment. Setting Health assessment was undertaken at one of two dedicated health assessment centers or in the study participant's home if travel was not practicable. Participants Five t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

17
151
3
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 174 publications
(173 citation statements)
references
References 31 publications
17
151
3
2
Order By: Relevance
“…Consistent with previous findings, older age was associated with lower scores [11][12][13][14][15][16][17][18][31][32][33][34][35]. We found a 1.0-point difference between the youngest (65-75) and oldest (75-85) groups; other studies have reported a difference of 0.6-2.4 points between similar age groups [13,[15][16][17]31].…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…Consistent with previous findings, older age was associated with lower scores [11][12][13][14][15][16][17][18][31][32][33][34][35]. We found a 1.0-point difference between the youngest (65-75) and oldest (75-85) groups; other studies have reported a difference of 0.6-2.4 points between similar age groups [13,[15][16][17]31].…”
Section: Discussionsupporting
confidence: 81%
“…We found a 1.0-point difference between the youngest (65-75) and oldest (75-85) groups; other studies have reported a difference of 0.6-2.4 points between similar age groups [13,[15][16][17]31]. Lower level of education was significantly associated with lower scores, correlating with results from other studies [11][12][13][14][15][16][17][18][31][32][33][34][35]. The difference in mean score was 1.4 points between the least and highest educated groups, in agreement with the original suggested method of adding an extra point for low education (≤12 years).…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…dementia) 7 . The complex abilities of processing internal and environmental information, establishing and achieving goals, solving problems and making decisions are known as executive functions 12,13,14,15 . Highly-educated individuals have better performances on executive function tasks.…”
mentioning
confidence: 99%
“…Four categories were defined: normal B12/normal folate (total cobalamin >258 pmol/L, folate < = 45·3 nmol/L) low B12/normal folate (total cobalamin < = 258 pmol/L, folate < = 45·3 nmol/L), low B12/high folate (total cobalamin < = 258 pmol/L, folate >45·3 nmol/L), and normal B12/high folate (total cobalamin >258 pmol/L, folate >45·3 nmol/L). The Mini-Mental State Examination (MMSE), the Montreal Cognitive Assessment (MoCA) and verbal fluency were used was used to assess cognitive performance (3) . Multiple regression analyses were used to examine relationship of each category with these measures of cognitive function.…”
mentioning
confidence: 99%